2011
DOI: 10.1108/17538391111144533
|View full text |Cite
|
Sign up to set email alerts
|

The financial performance of Saudi Arabian IPOs

Abstract: PurposeThe main objective of this paper is to measure Saudi Arabian initial public offerings' (IPOs) financial performance before and after going public on the Saudi Stock Exchange Market. The paper also aims to explore factors associated with the financial performance variation between pre‐ and post‐IPO.Design/methodology/approachA sample of 16 Saudi IPOs is investigated. A matched pairs methodology is mainly used combined with regression analysis.FindingsSaudi IPOs exhibit a significant decline in the post‐I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…countries studied. The said initial return is calculated based on the following two studies namely, Ahmed S. Alanazi et al (2011) and Faisal Alqahtani (2011) for a total of 80 IPOs in the period of 2003 to 2011. A more recent study in Saudi Arabia was conducted by Mayes and Alqahtani (2015) for 72 IPO companies between 2004 and September 2010.…”
Section: Underpricing Of Short-run Iposmentioning
confidence: 99%
See 2 more Smart Citations
“…countries studied. The said initial return is calculated based on the following two studies namely, Ahmed S. Alanazi et al (2011) and Faisal Alqahtani (2011) for a total of 80 IPOs in the period of 2003 to 2011. A more recent study in Saudi Arabia was conducted by Mayes and Alqahtani (2015) for 72 IPO companies between 2004 and September 2010.…”
Section: Underpricing Of Short-run Iposmentioning
confidence: 99%
“…Closer to home, in Saudi Arabia, among the early attempts at formal analysis of IPO performance, Ahmed S. Alanazi et al (2011) compared the pre-and post IPO financial performance of 16 companies that went public between 2003 and 2009. Using two accounting measures, namely, the return on assets (ROA) and return on sales (ROS), their analysis suggests that both financial measures fell significantly after the IPO.…”
Section: Long-run Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Almost all studies on performance assessment of IPOs in emerged and emerging markets have found that accounting performance of IPOs becomes a significant decline post-IPO relative to pre-IPO (e.g. Jain, Kini 1994;Mikkelson et al 1997;Kim et al 2004;Wang 2005;Alanazi et al 2011;Alanazi, Liu 2013). According to Jain and Kini (1994) who examine the ABP of US IPOs, accounting performance of the post-IPO has been declining.…”
Section: Firm Performance and Iposmentioning
confidence: 99%
“…They also focus on the effect of ownership and ownership concentration on IPO performance changes, and find that there is no relation between them. Alanazi et al (2011) has measured the financial performance of Saudi IPOs by using two ABP measures (ROA and ROS) to explore factors associated with the financial performance variation between pre-and post-IPO. Their result is also similar as the above-mentioned studies since they find that Saudi IPOs exhibit a sharp decline in the post-IPO performance compared to the pre-IPO period.…”
Section: Firm Performance and Iposmentioning
confidence: 99%